Designing of multimedia learning using lectora inspire for informatics education students - Elfi Tasrif (Jurnal Konseling dan Pendidikan, 2021)
Learning is more interesting and helps foster a sense of enthusiasm for learning is the role of multimedia. This study aims to design multimedia learning on the subject of Computer Networks and Data Communication for informatics education students. This type of research uses a development research approach, this research will only focus on stage I, namely designing multimedia learning. Designing multimedia learning in computer networking and data communications subject using Lectora Inspire Software. Furthermore, validation is carried out based on expert trials, on aspects of software engineering, aspects of application design, aspects of visual communication. The results of designing multimedia learning in the subject of Computer Networks and Data Communication for informatics education students are valid, feasible, easy to use, and very friendly. So that with this multimedia learning design greatly contributes to learning in informatics education.